Fracture, Fatigue, Failure and Damage Evolution, Volume 7 Proceedings of the 2017 Annual Conference on Experimental and Applied Mechanics (Conference Proceedings of the Society for Experimental Mechanics Series,, 2018)
Fracture, Fatigue, Failure and Damage Evolution, Volume 7 of the Proceedings of the 2017 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the seventh volume of nine from the Conference, brings together contributions to this important area of research and engineering. Session organizers include: Jay Carroll, Shuman Xia, Allison Beese, Ryan Berke, Garrett Pataky, Samantha Daly, Kavan Hazeli, Antonios Kontsos,Omer Ozgur Capraz, Scott Grutzik, Onome Scott-Emaukpor The collection presents early findings and case studies on a wide range of areas, including: Mechanics of Energy & Energetic Materials Vibration Effects in Fracture & Fatigue Fracture & Fatigue of Additively Manufactured Materials In Situ Techniques for Fatigue & Fracture Microscale & Microstructural Effects on Mechanical Behavior Fracture & Fatigue of Composites Integration & Validation of Models with Experiments Fracture & Fatigue in Extreme Environments Novel Experimental Methods for Fatigue and Fracture Fracture of Brittle & Ductile Materials Interfacial Fracture.